PROFIL MINAT BELAJAR PESERTA DIDIK KELAS X DAN IMPLIKASINYA DALAM PELAYANAN BIMBINGAN DAN KONSELING DI SMK NEGERI 7 PADANG - Tyara Anggraini; Wira Solina; Joni Adison (Jurnal Manajemen Pendidikan, 2026)
This research is motivated by the low desire, interest, participation, understanding, and attention of students in participating in learning in class X of SMKN 7 Padang. This condition shows the need to map the profile of students' learning interests as the basis for planning more targeted Guidance and Counseling services. This study aims to determine the profile of students' learning interests based on the desire to participate in learning, interest in learning activities, active participation, understanding in participating in learning, and attention in other learning activities. The study used a quantitative descriptive approach with a population of 216 students and a sample of 60 people selected through the purposive simple random sampling technique. The research instrument was in the form of a learning interest questionnaire with 44 statements. Data analysis was carried out using analysis requirements test and descriptive analysis. The results showed that students' interest in learning was in the very high category in the aspect of wanting to participate in learning, understanding, and attention, as well as in the high category in the aspect of interest and participation. The results of this study are recommended as a basis for BK teachers in providing classical services related to the development of learning attitudes and disciplines.